Live-cell imaging reveals decreased cAMP in a PFE-associated c.1050-3C>G PTH1R cell model - K. Marnet; H. Subramanian; M. Wiesler; A. Borst; D. Liedtke; G. Pattappa; D. Docheva; V. O. Nikolaev; A. Stellzig-Eisenhauer; M. Eigenthaler; M. Herrmann (Journal of Molecular Medicine, 2026)
Primary failure of eruption (PFE) is a rare autosomal disorder provoked by heterozygous mutations in the parathyroid hormone receptor 1 ( PTH1R ) gene. PTH1R is a G protein-coupled receptor (GPCR) which regulates intracellular signaling molecules like cAMP. By using CRISPR/Cas9, the pathogenic PTH1R variant, c.1050-3C>G, was introduced into the periodontal ligament (PDL-hTERT) cell line to investigate molecular mechanisms in a PFE in vitro model. The PDL-hTERT immortal cell line, derived from human primary PDL cells, is a well-established model for dental diseases and expresses PTH1R . We performed different functional assays to compare the behavior of the PDL-hTERT WT versus PTH1R -mutated cells. cAMP synthesis and PKA activation were compared between different cell lines by live-cell imaging using Förster Resonance Energy Transfer (FRET)-based biosensors. Phosphorylation of VASP was measured to validate and compare the PKA activation between the cell lines. In summary, our experiments show that the mutated cell line has no major phenotypic changes, but the PTH1R downstream signaling cascade is impaired. Key messages A rare autosomal disorder linked to mutations in the PTH1R gene, which encodes a G protein-coupled receptor regulating intracellular signaling, including cAMP production. The pathogenic PTH1R mutation (c.1050-3C>G) was introduced into a periodontal ligament (PDL hTERT) cell line to model PFE and study molecular mechanisms in vitro. Functional assay revealed that while the mutated cell line displayed no major phenotypic changes, the PTH1R downstream signaling cascade, including cAMP synthesis and PKA activation, was disrupted. Techniques like FRET-based biosensors and VASP phosphorylation assays highlighted specific impairments in signaling pathways in cells with the PTH1R mutations

Present-Day Sea Level Variations in Coastal Areas from Daily to Multidecadal Time Scales: Observations and Causes - A. Cazenave; R. Almar; P. Almeida; N. K. Ayoub; J. H. Bettencourt; F. Birol; W. Han; M. Herrmann; S. Jevrejeva; L. Leclercq; F. Niño; J. Oelsmann; et al. (Surveys in Geophysics, 2026)

Quantifying microplastics and their retention in greywater treatment systems of different scales - M. Sami; A. Hedström; H. Österlund; E. Kvarnström; P.D. Jenssen; M. Hartl; I. Herrmann (Journal of Hazardous Materials, 2026)

Environmental DNA reveals potential trophic links at male sperm whale foraging sites in Northern Norway - Hannah Maria Iversen Benton; Ove Mikal Pedersen; Zoë Morange; Yannick Herrmann; Daniel Kumazawa Morais; Kim Præbel; Audun H. Rikardsen; Mads Reinholdt Jensen (Frontiers in Marine Science, 2026)
Diet- and trophic studies involving whales are often challenging, particularly for deep-diving species that are difficult to observe while feeding. Recently, environmental DNA (eDNA) techniques relying on water samples have been increasingly used to describe biodiversity patterns in marine ecosystems. These methods also show promise for examining trophic interactions and identifying potential prey for whales. Here, we used eDNA metabarcoding to investigate fish communities that could serve as direct or indirect food resources for deep-diving sperm whales ( Physeter macrocephalus ) during March in a productive area off the coast of Northern Norway. The eDNA results were compared to dive behavior data from sperm whales instrumented with archival tags in the same area, while whale presence was assessed using a combination of eDNA, visual observations, and acoustic monitoring. We found significant differences in fish community composition along the transects, with most samples dominated by herring ( Clupea sp.) and capelin ( Mallotus villosus ), representing ≥50% relative abundance for most samples. These species spawn in the area during February–March, likely attracting known sperm whale prey species such as cod ( Gadus morhua ), redfish ( Sebastes sp.), and Greenland halibut ( Reinhardtius hippoglossoides ), which were also detected in high relative abundance at presumed sperm whale foraging depths. Our findings suggest that capelin and herring indirectly increase sperm whale abundance in the area by attracting more suitable prey during early spring. This study highlights the potential of eDNA techniques as a non-invasive tool for identifying co-occurrence patterns potentially indicative of trophic interactions and for elucidating the ecological roles of deep-diving whales.

Ecosystem Metabolic Rates Estimated from Diel Oxygen Measurements in Two Subtropical Estuaries - J. M. Arriola; R. G. Najjar; H. Briceño; C. Hu; M. Herrmann; M. W. Beck (Estuaries and Coasts, 2025)
Subtropical estuaries worldwide are facing increasing pressure from human population growth, development, and climate change. Carbon is a useful currency for understanding how estuaries respond to these pressures and yet relatively little is known about carbon cycling in subtropical estuaries. Here we compute gross primary production (GPP), ecosystem respiration (ER), and net ecosystem production (NEP) from the diurnal cycle in dissolved oxygen measured during 38 week-long individual deployments over three years in two estuaries in the southeastern United States, Biscayne Bay and Tampa Bay. On average for both estuaries, GPP and ER nearly balance, with NEP about an order of magnitude smaller. Even though production in Tampa Bay and Biscayne Bay is dominated by different primary producers and limiting nutrients, mean GPP was the same, about 190 mmol O 2 m –2 d –1 (570 g C m –2 y –1 ). Our GPP estimates for Biscayne Bay are more than an order of magnitude greater than the only other productivity estimates available for this system, which are planktonic net primary productivity measurements from the late 1970s. GPP was strongly correlated with water temperature in Biscayne Bay ( r = 0.60) but had the strongest correlation with salinity in Tampa Bay ( r = 0.39). These findings highlight the importance of more frequent production measurements in these complex estuaries, especially in the face of a changing climate.

P29-02 Comparative assessment of 24 poorly soluble, low toxicity dusts after short-term exposure - A. Herrmann; L. Puente; M. Dammann; L. Ma-Hock; H. Stratmann (Toxicology Letters, 2025)

Soil access is an equity issue for urban climate resilience - Adam Berland; Dustin L. Herrmann; Dexter H. Locke; Kirsten Schwarz (Landscape and Urban Planning, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Local fractal dimension of collagen detects increased spatial complexity in fibrosis - Dylan T. Casey; Karolyn G. Lahue; Vitor Mori; Jacob Herrmann; Joseph K. Hall; Béla Suki; Yvonne M. W. Janssen-Heininger; Jason H. T. Bates (Histochemistry and Cell Biology, 2024)
Increase of collagen content and reorganization characterizes fibrosis but quantifying the latter remains challenging. Spatially complex structures are often analyzed via the fractal dimension; however, established methods for calculating this quantity either provide a single dimension for an entire object or a spatially distributed dimension that only considers binary images. These neglect valuable information related to collagen density in images of fibrotic tissue. We sought to develop a fractal analysis that can be applied to 3-dimensional (3D) images of fibrotic tissue. A fractal dimension map for each image was calculated by determining a single fractal dimension for a small area surrounding each image pixel, using fiber thickness as the third dimension. We found that this local fractal dimension increased with age and with progression of fibrosis regardless of collagen content. Our new method of distributed 3D fractal analysis can thus distinguish between changes in collagen content and organization induced by fibrosis.

Cadmium Reduction in Spring Wheat: Root Exudate Composition Affects Cd Partitioning Between Roots and Shoots - M. C. Affholder; A. A. Moazzami; M. Weih; H. Kirchmann; A. M. Herrmann (Journal of Soil Science and Plant Nutrition, 2023)
Cadmium (Cd) in cereals is one of the major sources of Cd intake by human diets, and solutions to reduce Cd concentrations in wheat still need to be developed. Plant breeding, by selecting low-Cd varieties, can be an important tool to reduce Cd in crops. Knowing the genotypic variation in Cd accumulation and furthering our understanding of the impact of root exudates composition on Cd accumulation in crops may provide valuable information for plant breeding. In this study, we selected nine spring wheat varieties and analysed the accumulation and distribution of Cd in shoots, roots, root surfaces and kernels in relation to their qualitative and quantitative composition of root exudates, determined by 1 H-NMR (Proton Nuclear Magnetic Resonance). Results showed that the Cd concentration in shoots at an early stage could be used as a predictor for Cd concentration in kernels. Total Cd uptake was not correlated to the mobility of Cd in the rhizosphere, but total Cd was negatively correlated to Cd adsorbed at the root surface. Furthermore, (i) exudation of organic acids (primarily succinate and acetate) increased Cd concentration in shoots, and (ii) exudation of nucleosides, DNA (deoxyribonucleic acid) degradation products, increased Cd adsorption at the root surface. Therefore, root exudates composition should be taken into account when selecting for low-Cd wheat traits.

Impact of ground gear design on catch efficiency in demersal trawl fishery - Y.E. Fakıoğlu; G. Gökçe; H. Özbilgin; K. Cerbule; B. Herrmann (Regional Studies in Marine Science, 2023)

Applying hyperspectral transmittance for inter-genera classification of cyanobacterial and algal cultures - Olubunmi E. Adejimi; Giji Sadhasivam; Ze'ev Schmilovitch; Orr H. Shapiro; Ittai Herrmann (Algal Research, 2023)

Residential land owner type mediates the connections among vacancy, overgrown vegetation, and equity - Adam Berland; Dexter H. Locke; Dustin L. Herrmann; Kirsten Schwarz (Urban Forestry & Urban Greening, 2023)

Cognitive control, interference inhibition, and ordering of information during working memory in younger and older healthy adults - Mina Mirjalili; Reza Zomorrodi; Zafiris J. Daskalakis; Sean L. Hill; Sanjeev Kumar; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Nathan Herrmann; Krista L. Lanctôt; Linda Mah; Benoit H. Mulsant; et al. (GeroScience, 2022)

Evaluation of biotransformation capacity of transplastomic plants and hairy roots of Nicotiana tabacum expressing human cytochrome P450 2D6 - Y. V. Sheludko; I. M. Gerasymenko; F. J. Herrmann; H. Warzecha (Transgenic Research, 2022)
Cytochrome P450 monooxygenases (CYPs) are important tools for regio- and stereoselective oxidation of target molecules or engineering of metabolic pathways. Functional heterologous expression of eukaryotic CYPs is often problematic due to their dependency on the specific redox partner and the necessity of correct association with the membranes for displaying enzymatic activity. Plant hosts offer advantages of accessibility of reducing partners and a choice of membranes to insert heterologous CYPs. For the evaluation of plant systems for efficient CYP expression, we established transplastomic plants and hairy root cultures of Nicotiana tabacum carrying the gene encoding human CYP2D6 with broad substrate specificity. The levels of CYP2D6 transcript accumulation and enzymatic activity were estimated and compared with the data of CYP2D6 transient expression in N. benthamiana . The relative level of CYP2D6 transcripts in transplastomic plants was 2–3 orders of magnitude higher of that observed after constitutive or transient expression from the nucleus. CYP2D6 expressed in chloroplasts converted exogenous synthetic substrate loratadine without the need for co-expression of the cognate CYP reductase. The loratadine conversion rate in transplastomic plants was comparable to that in N. benthamiana plants transiently expressing a chloroplast targeted CYP2D6 from the nucleus, but was lower than the value reported for transiently expressed CYP2D6 with the native endoplasmic reticulum signal-anchor sequence. Hairy roots showed the lowest substrate conversion rate, but demonstrated the ability to release the product into the culture medium. The obtained results illustrate the potential of plant-based expression systems for exploiting the enzymatic activities of eukaryotic CYPs with broad substrate specificities.

Deformation Experiments on Bowland and Posidonia Shale—Part II: Creep Behavior at In Situ pc–T Conditions - J. Herrmann; E. Rybacki; H. Sone; G. Dresen (Rock Mechanics and Rock Engineering, 2020)

Recovering Brain Dynamics During Concurrent tACS-M/EEG: An Overview of Analysis Approaches and Their Methodological and Interpretational Pitfalls - Florian H. Kasten; Christoph S. Herrmann (Brain Topography, 2019)

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

A one year study of functionalised medium-chain carboxylic acids in atmospheric particles at a rural site in Germany revealing seasonal trends and possible sources - M. Teich; D. van Pinxteren; H. Herrmann (Journal of Atmospheric Chemistry, 2019)

Deformation Experiments on Bowland and Posidonia Shale—Part I: Strength and Young’s Modulus at Ambient and In Situ pc–T Conditions - J. Herrmann; E. Rybacki; H. Sone; G. Dresen (Rock Mechanics and Rock Engineering, 2018)

ForC: a global database of forest carbon stocks and fluxes - Kristina J. Anderson‐Teixeira; Maria M. H. Wang; Jennifer C. McGarvey; Valentine Herrmann; Alan J. Tepley; Ben Bond‐Lamberty; David S. LeBauer (Ecology, 2018)
Forests play an influential role in the global carbon (C) cycle, storing roughly half of terrestrial C and annually exchanging with the atmosphere more than five times the carbon dioxide ( CO 2 ) emitted by anthropogenic activities. Yet, scaling up from field‐based measurements of forest C stocks and fluxes to understand global scale C cycling and its climate sensitivity remains an important challenge. Tens of thousands of forest C measurements have been made, but these data have yet to be integrated into a single database that makes them accessible for integrated analyses. Here we present an open‐access global Forest Carbon database (ForC) containing previously published records of field‐based measurements of ecosystem‐level C stocks and annual fluxes, along with disturbance history and methodological information. ForC expands upon the previously published tropical portion of this database, TropForC ( https://doi.org/10.5061/dryad.t516f ), now including 17,367 records (previously 3,568) representing 2,731 plots (previously 845) in 826 geographically distinct areas. The database covers all forested biogeographic and climate zones, represents forest stands of all ages, and currently includes data collected between 1934 and 2015. We expect that ForC will prove useful for macroecological analyses of forest C cycling, for evaluation of model predictions or remote sensing products, for quantifying the contribution of forests to the global C cycle, and for supporting international efforts to inventory forest carbon and greenhouse gas exchange. A dynamic version of ForC is maintained at on GitHub ( https://GitHub.com/forc-db ) , and we encourage the research community to collaborate in updating, correcting, expanding, and utilizing this database. ForC is an open access database, and we encourage use of the data for scientific research and education purposes. Data may not be used for commercial purposes without written permission of the database PI . Any publications using ForC data should cite this publication and Anderson‐Teixeira et al. (2016a) (see Metadata S1 ). No other copyright or cost restrictions are associated with the use of this data set.

Measurements of PM10 ions and trace gases with the online system MARGA at the research station Melpitz in Germany – A five-year study - B. Stieger; G. Spindler; B. Fahlbusch; K. Müller; A. Grüner; L. Poulain; L. Thöni; E. Seitler; M. Wallasch; H. Herrmann (Journal of Atmospheric Chemistry, 2018)

Peripheral Alterations in Cytokine and Chemokine Levels After Antidepressant Drug Treatment for Major Depressive Disorder: Systematic Review and Meta-Analysis - Cristiano A. Köhler; Thiago H. Freitas; Brendon Stubbs; Michael Maes; Marco Solmi; Nicola Veronese; Nayanna Q. de Andrade; Gerwyn Morris; Brisa S. Fernandes; André R. Brunoni; Nathan Herrmann; Charles L. Raison; et al. (Molecular Neurobiology, 2017)

HC-Induced Deactivation in CO Conversion at Diesel Oxidation Catalysts - M. Herrmann; S. Malmberg; A. Drochner; H. Vogel; R. Hayes; M. Votsmeier (Emission Control Science and Technology, 2016)

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

A chamber study on the reactions of O3, NO, NO2 and selected VOCs with a photocatalytically active cementitious coating material - F. Mothes; O. Böge; H. Herrmann (Environmental Science and Pollution Research, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Differential Accumulation of Mercury and Selenium in Brown Trout Tissues of a High-Gradient Urbanized Stream in Colorado, USA - S. J. Herrmann; D. R. Nimmo; J. S. Carsella; L. M. Herrmann-Hoesing; J. A. Turner; J. M. Gregorich; B. D. Vanden Heuvel; R. B. Nehring; H. P. Foutz (Archives of Environmental Contamination and Toxicology, 2016)

Accumulation of Traffic-Related Trace Metals in Urban Winter-Long Roadside Snowbanks - S. Moghadas; K. H. Paus; T. M. Muthanna; I. Herrmann; J. Marsalek; M. Viklander (Water, Air, & Soil Pollution, 2015)

Photocatalytic abatement results from a model street canyon - M. Gallus; R. Ciuraru; F. Mothes; V. Akylas; F. Barmpas; A. Beeldens; F. Bernard; E. Boonen; A. Boréave; M. Cazaunau; N. Charbonnel; H. Chen; et al. (Environmental Science and Pollution Research, 2015)

How neutrophil extracellular traps orchestrate the local immune response in gout - Christian Maueröder; Deborah Kienhöfer; Jonas Hahn; Christine Schauer; Bernhard Manger; Georg Schett; Martin Herrmann; Markus H Hoffmann (Journal of Molecular Medicine, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Emission of N2O from Biogas Crop Production Systems in Northern Germany - Mehmet Senbayram; Ruirui Chen; Babette Wienforth; Antje Herrmann; Henning Kage; Karl H. Mühling; Klaus Dittert (BioEnergy Research, 2014)

Modelling multiphase chemistry in deliquescent aerosols and clouds using CAPRAM3.0i - A. Tilgner; P. Bräuer; R. Wolke; H. Herrmann (Journal of Atmospheric Chemistry, 2013)

Feedbacks underlie the resilience of salt marshes and rapid reversal of consumer‐driven die‐off - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Eric E. Axelman; Nicholas C. Herrmann; P. Lauren Szathmary (Ecology, 2013)
Understanding ecosystem resilience to human impacts is critical for conservation and restoration. The large‐scale die‐off of New England salt marshes was triggered by overfishing and resulted from decades of runaway crab grazing. In 2009, however, cordgrass began to recover, decreasing die‐off ∼40% by 2010. We used surveys and experiments to test whether plant–substrate feedbacks underlie marsh resilience. Initially, grazer‐generated die‐off swept through the cordgrass, creating exposed, stressful peat banks that inhibited plant growth. This desertification cycle broke when banks eroded and peat transitioned into mud with fewer herbivores, less grazing, and lower physical stress. Cordgrass reestablished in these areas through a feedback where it engineered a recovery zone by further ameliorating physical stresses and facilitating additional revegetation. Our results reveal that feedbacks can play a critical role in rapid, reversible ecosystem shifts associated with human impacts, and that the interplay of facilitative and consumer interactions should be incorporated into resilience theory.

Long-term size-segregated particle (PM10, PM2.5, PM1) characterization study at Melpitz -- influence of air mass inflow, weather conditions and season - G. Spindler; A. Grüner; K. Müller; S. Schlimper; H. Herrmann (Journal of Atmospheric Chemistry, 2013)

Size-segregated characterization of PM10 at the EMEP site Melpitz (Germany) using a five-stage impactor: a six year study - G. Spindler; T. Gnauk; A. Grüner; Y. Iinuma; K. Müller; S. Scheinhardt; H. Herrmann (Journal of Atmospheric Chemistry, 2012)

A trophic cascade triggers collapse of a salt‐marsh ecosystem with intensive recreational fishing - Andrew H. Altieri; Mark D. Bertness; Tyler C. Coverdale; Nicholas C. Herrmann; Christine Angelini (Ecology, 2012)
Overexploitation of predators has been linked to the collapse of a growing number of shallow‐water marine ecosystems. However, salt‐marsh ecosystems are often viewed and managed as systems controlled by physical processes, despite recent evidence for herbivore‐driven die‐off of marsh vegetation. Here we use field observations, experiments, and historical records at 14 sites to examine whether the recently reported die‐off of northwestern Atlantic salt marshes is associated with the cascading effects of predator dynamics and intensive recreational fishing activity. We found that the localized depletion of top predators at sites accessible to recreational anglers has triggered the proliferation of herbivorous crabs, which in turn results in runaway consumption of marsh vegetation. This suggests that overfishing may be a general mechanism underlying the consumer‐driven die‐off of salt marshes spreading throughout the western Atlantic. Our findings support the emerging realization that consumers play a dominant role in regulating marine plant communities and can lead to ecosystem collapse when their impacts are amplified by human activities, including recreational fishing.

A study to discriminate local, urban and regional source contributions to the particulate matter concentrations in the city of Dresden, Germany - T. Gnauk; K. Müller; E. Brüggemann; W. Birmili; K. Weinhold; D. van Pinxteren; G. Löschau; G. Spindler; H. Herrmann (Journal of Atmospheric Chemistry, 2011)

Differential effects of habitat isolation and landscape composition on wasps, bees, and their enemies - Christof Schüepp; John D. Herrmann; Felix Herzog; Martin H. Schmidt-Entling (Oecologia, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Female-biased incubation and strong diel sex-roles in the Two-banded Plover Charadrius falklandicus - James J. H. St Clair; Philipp Herrmann; Robin W. Woods; Tamás Székely (Journal of Ornithology, 2010)

Inefficient clearance of dying cells in patients with SLE: anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kristin Kruse; Christina Janko; Vilma Urbonaviciute; Claudia T. Mierke; Thomas H. Winkler; Reinhard E. Voll; Georg Schett; Luis E. Muñoz; Martin Herrmann (Apoptosis, 2010)

Thermodynamic properties of sea air - R. Feistel; D. G. Wright; H.-J. Kretzschmar; E. Hagen; S. Herrmann; R. Span (Ocean Science, 2010)
Very accurate thermodynamic potential functions are available for fluid water, ice, seawater and humid air covering wide ranges of temperature and pressure conditions. They permit the consistent computation of all equilibrium properties as, for example, required for coupled atmosphere-ocean models or the analysis of observational or experimental data. With the exception of humid air, these potential functions are already formulated as international standards released by the International Association for the Properties of Water and Steam (IAPWS), and have been adopted in 2009 for oceanography by IOC/UNESCO. In this paper, we derive a collection of formulas for important quantities expressed in terms of the thermodynamic potentials, valid for typical phase transitions and composite systems of humid air and water/ice/seawater. Particular attention is given to equilibria between seawater and humid air, referred to as "sea air" here. In a related initiative, these formulas will soon be implemented in a source-code library for easy practical use. The library is primarily aimed at oceanographic applications but will be relevant to air-sea interaction and meteorology as well. The formulas provided are valid for any consistent set of suitable thermodynamic potential functions. Here we adopt potential functions from previous publications in which they are constructed from theoretical laws and empirical data; they are briefly summarized in the appendix. The formulas make use of the full accuracy of these thermodynamic potentials, without additional approximations or empirical coefficients. They are expressed in the temperature scale ITS-90 and the 2008 Reference-Composition Salinity Scale.

The Role of Disaggregation of Asset Values in Flood Loss Estimation: A Comparison of Different Modeling Approaches at the Mulde River, Germany - Anja Wünsch; Ulrich Herrmann; Heidi Kreibich; Annegret H. Thieken (Environmental Management, 2009)

Complete nucleotide sequence of the Oenothera elata plastid chromosome, representing plastome I of the five distinguishable Euoenothera plastomes - H. Hupfer; M. Swiatek; S. Hornung; R. G. Herrmann; R. M. Maier; W.-L. Chiu; B. Sears (Molecular Genetics and Genomics, 2008)

Endoparasite spectrum of wild cats (Felis silvestris Schreber, 1777) and domestic cats (Felis catus L.) from the Eifel, Pfalz region and Saarland, Germany - O. Krone; O. Guminsky; H. Meinig; M. Herrmann; M. Trinzen; G. Wibbelt (European Journal of Wildlife Research, 2008)

Molecular diagnosis of pulmonary tuberculosis by automated extraction and real-time PCR on non-decontaminated pulmonary specimens - V. Drouillon; P. H. Lagrange; J.-L. Herrmann (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

A source study of PM in Saxony by Size-Segregated Characterisation - H. Herrmann; E. Brüggemann; U. Franck; T. Gnauk; G. Löschau; K. Müller; A. Plewka; G. Spindler (Journal of Atmospheric Chemistry, 2006)

Root-to-shoot signalling: apoplastic alkalinization, a general stress response and defence factor in barley (Hordeum vulgare) - H. H. Felle; A. Herrmann; R. Hückelhoven; K.-H. Kogel (Protoplasma, 2005)

Induction of apoptosis by spermine-metabolites in primary human blood cells and various tumor cell lines - M. Schiller; N. Blank; P. Heyder; M. Herrmann; U. S. Gaipl; J. R. Kalden; H. M. Lorenz (Apoptosis, 2005)

Frequency of Norovirus in stool samples from patients with gastrointestinal symptoms in Switzerland - R. Fretz; L. Herrmann; A. Christen; P. Svoboda; O. Dubuis; E. H. Viollier; M. Tanner; A. Baumgartner (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Size-Resolved Aerosol Characterization for a Polluted Episode at the IfT Research Station Melpitz in Autumn 1997 - A. Plewka; T. Gnauk; E. Brüggemann; C. Neusüss; H. Herrmann (Journal of Atmospheric Chemistry, 2004)

Effects of selective inactivation of individual genes for low-molecular-mass subunits on the assembly of photosystem II, as revealed by chloroplast transformation: the psbEFLJ operon in Nicotiana tabacum - M. Swiatek; R. E. Regel; J. Meurer; G. Wanner; H. B. Pakrasi; I. Ohad; R. G. Herrmann (Molecular Genetics and Genomics, 2003)

Molecular analysis of aerobic phenylacetate degradation in Azoarcus evansii - R. Rost; S. Haas; E. Hammer; H. Herrmann; G. Burchhardt (Molecular Genetics and Genomics, 2002)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

C-to-U conversion in the intercistronic ndhI/ndhG RNA of plastids from monocot plants: conventional editing in an unconventional small reading frame? - A. Drescher; H. Hupfer; C. Nickel; F. Albertazzi; U. Hohmann; R. Herrmann; R. Maier (Molecular Genetics and Genomics, 2002)

The cyo operon of Pseudomonas putida is involved in carbon catabolite repression of phenol degradation - L. Petruschka; G. Burchhardt; C. Müller; C. Weihe; H. Herrmann (Molecular Genetics and Genomics, 2001)

Scenarios for Modeling Multiphase Tropospheric Chemistry - D. Poppe; B. Aumont; B. Ervens; H. Geiger; H. Herrmann; E.-P. Röth; W. Seidl; W. R. Stockwell; B. Vogel; S. Wagner; D. Weise (Journal of Atmospheric Chemistry, 2001)

The inverted repeats of IS1384, a newly described insertion sequence from Pseudomonas putida strain H, represent the specific target for integration of IS1383 - C. Müller; U. Lauf; H. Herrmann (Molecular Genetics and Genomics, 2001)

P300 and LORETA: Comparison of Normal Subjects and Schizophrenic Patients - G. Winterer; C. Mulert; S. Mientus; J. Gallinat; P. Schlattmann; H. Dorn; W.M. Herrmann (Brain Topography, 2001)

Role of apoptosis in autoimmunity - H-M. Lorenz; M. Herrmann; T. Winkler; U. Gaipl; J. R. Kalden (Apoptosis, 2000)

CAPRAM2.3: A Chemical Aqueous Phase Radical Mechanism for Tropospheric Chemistry - H. Herrmann; B. Ervens; H.-W. Jacobi; R. Wolke; P. Nowacki; R. Zellner (Journal of Atmospheric Chemistry, 2000)

Proving the Authenticity of Ancient DNA by Comparative Genomic Hybridization - S. Hummel; B. Herrmann; J. Rameckers; D. Müller; K. Sperling; H. Neitzel; H. Tönnies (The Science of Nature, 1999)

Diurnal changes in xylem pressure and mesophyll cell turgor pressure of the lianaTetrastigma voinierianum: The role of cell turgor in long-distance water transport - F. Thrmer; J. J. Zhu; N. Gierlinger; H. Schneider; R. Benkert; P. Gener; B. Herrmann; F. -W. Bentrup; U. Zimmerniann (Protoplasma, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Tissue culture of wild-type, interspecific genome/plastome hybrids and plastome mutants of evening primrose ( Oenothera) : controlled morphogenesis and transformation - A. Mehra-Palta; H.-U. Koop; S. Goes; E.-M. Troidl; G. Nagy; S. Tyagi; W. Kofer; R. G. Herrmann (Plant Cell Reports, 1998)

Plant regeneration from leaf protoplasts of evening primrose ( Oenothera hookeri ) - N. Kuchuk; R. G. Herrmann; H.-U. Koop (Plant Cell Reports, 1998)

UV-B Irradiated Cell Lines Execute Programmed Cell Death in Various Forms - M. Hagenhofer; H. Germaier; C. Hohenadl; P. Rohwer; J. R. Kalden; M. Herrmann (Apoptosis, 1998)

Intraepidemic variants of influenza virus H3 hemagglutinin differing in the number of carbohydrate side chains - W. Seidel; F. Knkel; B. Geisler; W. Garten; B. Herrmann; L. Dhner; H. -D. Klenk (Archives of Virology, 1991)